Improving drinking water quality in South Korea: A choice experiment - Adelina Gschwandtner; Cheul Jang; Richard McManus (University of Kent, School of Economics, 2017)
Increased pollution leads to a constant decrease of drinking water quality worldwide. Due to safety concerns, unpleasant taste and odour only about 3% of the population in South Korea is drinking untreated tap water. The present study uses choice experiments and cost-benefit analysis to investigate the feasibility of installing advanced water treatments in Cheongju waterworks in South Korea. The waterworks is situated in the middle of the country and is providing more than half a million people with drinking water. The study shows that the lower bound of the median WTP for installing a new advanced water treatment system is about 2 US/month, which is similar to the average expenditures for bottled water per household in South Korea. Scenarios under which the instalment of the advanced water treatments is feasible are discussed together with environmental solutions in the long-run
Keywords: C19; C83; C90; D12; D61; Q25; Q51; Q53; 330; Drinking Water Quality; Water Pollution; Choice Experiments; Willingness to Pay; Random Parameter and Latent Class Logit; Cost-Benefit Analysis